OPTIMAL CONDITIONS FOR FORMATION OF STUDENTS’ CREATIVE ACTIVITY IN THE LEARNING PROCESS IN HIGH SCHOOL - Ivanova, V.V. (Pedagogy of Higher and Secondary Education, 2009)
The optimal inner and outward conditions of high school students’ creative activity are being considered in the article.